PENGARUH SUHU BAHAN BAKAR TERHADAP KEPERLUAN BAHAN BAKAR PADA MOTOR DIESEL SATU SILINDER 20 HP DENGAN ELEKTROLISER - Sutomo, Sutomo; Murni, Murni; Rahmat, Rahmat (Vocational School Diponegoro University, 2011)
Sutomo, Murni, Rahmat, An internal combustion process of fuel will works effectively if the fuel’s density and viscosity is lower so we would like to use a heater in order to decrease the density and viscosity of the fuel. Based on this condition, we would like to use an electrolizer and a diesel engine to improve the fuel consumption. Electrolizer will increases the gas reaction so we hope that fuel consumption rate will decrease. The result of this research is the effective temperature of fuel is 50oC – 60oC will produce the effective combustion. The fuel consumption decreased in 6 kW is 0.12 lt/kWH. Key word: diesel engine, electrolizer, temperature